Foreword - Komlósi, István; Nagy, János (Acta Agraria Debreceniensis, 2018)
The higher education of economics and agriculture in Debrecen started 150 years ago. The historical roots of our institution reach back to the middle of the 19th century. In the 1850s, the wise leaders of the city of Debrecen realised that the development of agriculture is the sole opportunity which can make the region of the Tisza River and the Trans- Tisza region the most valuable pantry of the nation. Due to the generous support of the citizens of Debrecen, as well as the enthusiastic work of scientist and teachers, the National Higher Education Institute of Farming was established on 22nd October 1868 as the first agricultural higher education institution of the Great Hungarian Plain.